Sensitive method for the determination of rocilinostat in small volume mouse plasma by LC‐MS/MS and its application to a pharmacokinetic study in mice. (14th January 2016) - Gupta, Manish; Dixit, Abhishek; Devaraj, V. C.; Zainuddin, Mohd; Bhamidipati, Ravi Kanth; Hallur, Mahanandeesha S.; Dewang, Purushottam; Rajagopal, Sridharan; Rajagopal, Sriram; Mullangi, Ramesh
Abstract: A highly sensitive, specific and rapid LC‐ESI‐MS/MS method has been developed and validated for the quantification of rocilinostat in small volume mouse plasma (20 μL) using vorinostat as an internal standard (IS) as per regulatory guidelines. Sample preparation was accomplished through a protein precipitation procedure with acetonitrile. Chromatography was achieved on Prodigy ODS‐2 column using a binary gradient using mobile phase A (0.2% formic acid in water) and B (acetonitrile) at a flow rate of 0.38 mL/min. The total chromatographic run time was 4.1 min and the elution of rocilinostat and IS occurred at ~3.2 and 2.9 min, respectively. A linear response function was established in the concentration range of 0.28–1193 ng/mL in mouse plasma. The intra‐ and inter‐day accuracy and precisions were in the ranges of 3.12–8.93 and 6.41–11.6%, respectively. This novel method has been applied to a pharmacokinetic study in mice. Copyright © 2016 John Wiley & Sons, Ltd.